Maid to Order in Hong Kong : Stories of Migrant Workers, Second Edition - Constable, Nicole (Book collections on Project MUSE., 2007)
Middle-class Chinese women in the global city of Hong Kong have entered the workforce in unprecedented numbers over the past three decades, and the demand for foreign domestic workers has soared. A decade ago some foretold the decline in foreign workers and the influx of mainland workers. But today over 120,000 women from the Philippines, over 90,000 from Indonesia, and thousands more from other parts of South and Southeast Asia serve as maids on two-year contracts in Hong Kong, sending much needed remittances to their families abroad. Nicole Constable tells their story by updating Maid to Order in Hong Kong with a focus on the major changes that have taken place since Hong Kong's reunification with mainland China in 1997, the Asian financial crisis of the late 1990s, and the outbreak of SARS in 2002-2003. Interweaving her analysis with the women's individual stories, she shows how power is expressed in the day-to-day lives of Filipina domestic workers and more-recent Indonesian arrivals.